Family Interaction and Education in Fostering a Harmonious-Peaceful Family Within Islamic Law and Social Theory - Khoirus Sholeh (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2023)
This study describes a model of family interaction and education in fostering a harmonious, peaceful family within Islamic law and social theory. This research used a qualitative approach with a literature review design. Data were obtained through primary sources, including marriage laws and social interaction theory. The literature study data collection technique is a systematic process of gathering information from written sources. Based on the research analysis, efforts to foster a harmonious, peaceful, and happy family focus on open communication, attention, quality time together, and a lifestyle of simplicity and frugality. Several values that need to be cultivated in family education include physical strength, intellect, faith, morals, obligations, aesthetics, and social skills. Keywords: Social interaction, family education, harmony, peaceful